Risks in scientific research and some proposals on orientations for improving mechanism and policies in Vietnam - Cao Thi Hong Ngoc; Ha Cong Hai (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2025)
Risks are inherent in all spheres of human activity. However, in scientific research, risks are particularly prominent and intrinsic, because research involves exploration, discovery, and innovation, venturing into the unknown where both success and failure are possible. Risks in scientific research can manifest as failure to achieve the stated objectives, unreliable or contradictory results, a lack of practical impact, or ethical and legal violations. Research on risks in scientific research and proposals for improving mechanisms and policies is not a new issue, but it has recently garnered increasing attention from the research community due to the growing importance of the role and mission of science and technology (S&T) in the development and competitiveness of each nation. This article focuses on analysing the nature and causes of risks in scientific research, experience of some countries on mechanisms and policies for dealing with risks in scientific research, with specific reference to the context of Vietnam, and proposes directions for improving mechanisms and policies to manage risks in scientific research in Vietnam in the upcoming period. Code: 24121001